Attitudes of Nurses in Turkey Toward Care of Dying Individual and the Associated Religious and Cultural Factors - Karadag, Ezgi; Kilic, Serap Parlar; Ugur, Ozlem; Akyol, Merve Aliye (Springer, 2019)
The aim of this study was to determine the attitudes of nurses working in two university hospitals located in the west and east of Turkey toward care of dying individual as well as religious and cultural factors that influence their attitudes. The descriptive and comparative study was conducted with a total of 189 nurses who were working in adult inpatient clinics of two university hospitals in western (101 nurses) and eastern (88 nurses) Turkey between July and November 2016. The data were obtained by using the questionnaire and Frommelt Attitudes Toward Care of the Dying Scale. As a result of this study, it was determined that in terms of the status of receiving training the end-of-life care the majority of nurses received this training; however, this rate was higher (51.0%) in nurses working in the eastern hospital (p=0.025). The nurses working in the east (51.6%) were determined to have more problems during caregiving due to their religious and cultural beliefs, the most frequent problem they experienced was being uncomfortable due to privacy when giving care to patients from opposite gender (57.1%). The emotions felt mostly by nurses during the care of dying patient were grief (nurses in the east=48.5%, nurses in the west=51.5%) and despair (nurses in the east=40.4%, nurses in the west=59.6%). Nurses working both in the east (98.27 +/- 7.71) and in the west (97.19 +/- 8.99) were determined to have positive attitude toward death, and there was no statistically significant difference between both groups in terms of the mean scores of the Attitudes Toward Care of the Dying Scale (p=0.373). In accordance with these results, it is recommended to focus on death issues in end-of-life care during the nursing education and to support nurses with in-service trainings regularly after the graduation.
Keywords: Attitude toward death; Care of dying person; Religious and cultural factors; Nursing